Opioid Use Disorder and intracerebral hemorrhage in Isfahan, Iran: a case–control study - Saadatnia, Mohammad; Norouzi, Razieh; Najafi, Mohammad Amin; Gol Parvar, Sahand; Najafian, Arash; Tabatabei, Aryan; Foroughi, Melika; Esteki, Sadaf; Khorvash, Fariborz (Frontiers in Neurology, 2024)
Background Opium use disorder is a significant health problem in our country, leading to a considerable number of health issues. Opium has several detrimental effects on its consumers. However, the effect of Opium use disorder on intracerebral hemorrhage (ICH) has not been evaluated. This study aims to evaluate the relationship between Opium use disorder and ICH. Methods In this case–control study, 402 patients with ICH and 404 patients without ICH enrolled. Opium use disorder, other vascular risk factors including diabetes mellitus, hypertension, hyperlipidemia, and tobacco smoking was compared between these groups. Patients with ICH were divided into two groups; first group are patients with history of Opioid Use Disorder and second group are those patients without Opioid Use Disorder. ICH features including clinical and imaging characteristics and prognostic findings were compared between patients with and without Opium use disorder. Results This case–control study of 806 participants found that hypertension (OR = 6.84, 95% CI: 5.03–9.34, p-value: <0.001), Opium use disorder (OR = 4.23, 95% CI: 2.42–7.35, p-value: <0.001) and tobacco smoking (OR = 1.47, 95% CI: 1.01–2.16, p-value: 0.049) had a higher risk of ICH. Opium-addicted subjects had higher ICH scores (2.61 ± 1.27 vs. 2.11 ± 1.29, p-value: 0.005), were more likely to have infratentorial hemorrhage (22% vs. 12%, OR = 2.13, 95% CI: 1.06–4.28, p-value: 0.038), more likely to be intubated (66% vs. 54%, OR = 1.79, 95% CI: 0.98–3.27, p-value = 0.041) and had lower GCS scores (9.58 ± 3.60 vs. 8.25 ± 3.88, p-value: 0.01). The effect of Opium use disorder independently on ICH was also shown in logistic regression (adjusted OR = 3.15, p-value = 0.001). Conclusion This study is the first to evaluate the effect of Opium use disorder on ICH, identifying Opium use disorder as a new potential risk factor for ICH.